Interpretation Of Dreams In The Study Of Islamic Tasawuf - Syarifuddin; Zulfi Imran (Yayasan Multidimensi Kreatif, 2025)
Every human being who sleeps has ever dreamed , although many claim not to remember it when they wake up. Some people believe that dreaming will bring a sign. So, how is the interpretation of dreams in the study of Sufism? Dreams as a psychological and spiritual phenomenon has been a focus of human attention throughout history and has received special attention in literature, philosophy, Sufism, Mysticism and various religious traditions. Some people know dreams as Bunga tidur , where some people believe that dreams have meaning or as a sign. Is it true that dreams according to Sufism are also like that? In the development of human thought, dreams are considered as a gateway to the spiritual world, a place where experiences that go beyond the boundaries of physical reality are revealed. Despite their highly personal nature, dreams have an inescapable universal appeal in shaping human culture. The phenomenon of dreams, in all its aspects, is not a separate entity, but is closely interwoven with the cultural heritage and everyday life of human beings. Dreams can be seen as a reflection of the complexity of human thoughts and emotions. The existence of dreams does not only cover the individual realm, but also extends into the collective realm. Jungian psychology, for example, emphasizes the concept of the collective unconscious, where symbols and archetypes and interpretations in dreams reflect aspects that are universal and exist in all cultures of the world's people.